Overview of Spin Temperature, Thermal Mixing and Dynamic Nuclear Polarization - Goldman, M. (Applied magnetic resonance, 2008)
. The aim of this short article is to give a very schematic account of the main concepts associated with the spin temperature theory, in nuclear and in dilute electronic spin systems, and their applications to electron–nuclear thermal mixing as a mechanism of dynamic nuclear polarization. The body of existing theoretical and experimental material on these subjects is much too large to be described in any detail, and a selection can be found in the general references and in references therein.